No evidence for an adaptive role of early molt into breeding plumage in a female fairy wren. (11th December 2019) - Nolazco, Sergio; Hall, Michelle L; Kingma, Sjouke A; Delhey, Kaspar; Peters, Anne
Abstract: The evolution of ornaments as sexually selected signals is well understood in males, but female ornamentation remains understudied. Fairy wrens offer an excellent model system, given their complex social structure and mating systems, and the diversity of female ornamentation. We investigated whether early molt into ornamental breeding plumage plays an adaptive role in females of the monogamous purple-crowned fairy wren Malurus coronatus, the only fairy wren known to have female seasonal plumage. Using 6 years of monitoring, we found that the timing of female molt was similar to males, but there was no evidence for assortative mating. Like males (previous study), older and dominant individuals acquired their breeding plumage earlier; however, in contrast to males, early molt did not seem to be costly since unfavorable environmental conditions or previous reproductive effort did not delay molt. Early female molt was not associated with any indicator of reproductive quality nor did it attract additional offspring care by their partners. We also found no association between early molt and the likelihood of acquiring a dominant (breeding) position or with the presence or proximity to same-sex rivals. Our study results, which are similar to previous findings in conspecific males, suggest that directional selection for early molt might be relaxed in this species, in contrast to other genetically polygamous fairy wrens in which early molt predicts extrapair mating success in males. However, the finding that molt timing is status dependent raises the possibility that other attributes of the ornament may fulfill an adaptive function in females. Lay Summary: Early molt into seasonal ornamental plumage in male fairy wrens is often a signal to attract females. Here, we explore its function in female purple-crowned fairy wrens. Older and dominant females molted earlier, but we found no evidence to support an adaptive role of early molt in sexual or social selection contexts. Selection for early molt might be relaxed due to year-round territoriality and reproduction.